Analysis of the Influence of Trust and Its Antecedents (Forums and Communities, Interpersonal Recommendations, Social Presence, and Familiarity) on Purchase Intention on E-Commerce Platforms in Indonesia - Syahputra, Rizky; Anas Hidayat (Cita konsultindo, 2025)
This study aims to determine the effect of trust on purchase intention on e-commerce sites in Indonesia and the antecedent factors, namely forums and communities, interpersonal recommendations, social presence, and familiarity. Trust is a key element in online transactions that can influence consumer purchasing decisions. This study uses a quantitative method with a data collection technique through a survey of 300 respondents from e-commerce platform users in Indonesia. The sampling technique uses a non-probability sampling technique using a purposive sampling method which is then processed using the PLS-SEM statistical analysis tool using SmartPLS software version 3.0. The results of the study indicate that antecedent factors have a significant influence on the formation of consumer trust, which ultimately has an impact on increasing purchase intention. These findings provide insight for e-commerce industry players in designing strategies to increase consumer trust and engagement.